INFLUENCE OF PERFORMANCE CONTRACTING IN OPTIMIZING PROCUREMENT OF STATE CORPORATIONS IN KENYA - Agufa, Leonard Vwamu; Getuno, Dr. Pamela (International Journal of Supply Chain and Logistics, 2019)
Purpose: The specific objective of the study was to assess influence of performance contracting in optimizing procurement of state corporations in Kenya. Methodology: This research study adopted a descriptive research design approach targeting heads of procurement at the 187 state corporations. This method was preferred because it allowed an in-depth study of the subject. The study preferred this method because it allowed an in-depth study of the subject. To gather data, structured questionnaire will be used to collect data from 104 respondents. Data was collected using self-administered questionnaires. The data collected was analyzed by use of descriptive and inferential statistics. Multiple regression model was used to show the relationship between the dependent variable and the independent variables. The data generated was keyed in and analyzed by use of Statistical Package of Social Sciences (SPSS) version 21 to generate information which was presented using charts, frequencies and percentages. Results: The findings of the study indicated that; key performance indicators, monitoring and evaluation, balanced scorecard and administration structures have a positive relationship with procurement optimization of state corporations Conclusion: Based on the study findings, the study concludes that performance of state corporations can be improved by key performance indicators, monitoring and evaluation, balanced scorecard and administration structures. Policy recommendation: the study recommended that public institutions should embrace performance contracting practices so as to improve their procurement optimization and further researches should to be carried out in other public entities to find out if the same results can be obtained.